2015
DOI: 10.15252/embj.201490831
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle‐dependent ubiquitylation and destruction of NDE1 by CDK5‐FBW7 regulates ciliary length

Abstract: Primary cilia start forming within the G1 phase of the cell cycle and continue to grow as cells exit the cell cycle (G0). They start resorbing when cells re-enter the cell cycle (S phase) and are practically invisible in mitosis. The mechanisms by which cilium biogenesis and disassembly are coupled to the cell cycle are complex and not well understood. We previously identified the centrosomal phosphoprotein NDE1 as a negative regulator of ciliary length and showed that its levels inversely correlate with cilio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 69 publications
4
81
1
2
Order By: Relevance
“…Sequence of CDK5 siRNAs are as follow: UAUGACAGAAUCCCAGCCCTT, GGGCUGGGAUUCUGUCAUATT42. For efficient gene silencing, siRNAs were transfected twice.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence of CDK5 siRNAs are as follow: UAUGACAGAAUCCCAGCCCTT, GGGCUGGGAUUCUGUCAUATT42. For efficient gene silencing, siRNAs were transfected twice.…”
Section: Methodsmentioning
confidence: 99%
“…We showed that total CRMP2 and p-CRMP2 (Ser522) are increased in cystic disease and that the reduction of CDK5 leads to decreased level of both total CRMP2 and p-CRMP2. Interestingly, very recent findings by Maskey et al described intriguing involvement of CDK5 in regulating the FBW7-NDE1 pathway and its presumptive modulation of cilia length in a cell cycle-dependent manner, at least in vitro (54). It is possible that CDK5 may act through multiple downstream targets and therefore, its function in kidneys needs to be further investigated in subsequent studies in multiple disease settings.…”
Section: Discussionmentioning
confidence: 99%
“…Nde1, a paralogue of Ndel1, is highly expressed in mitotic cells but depleted during quiescence, and silencing of Nde1 in cultured cells and zebrafish leads to marked enhancement of cilium length and a delay in S phase entry 77 . Nde1 levels are controlled by CDK5 phosphorylation in G0/G1 cells, which targets Nde1 for ubiquitylation (and subsequent destruction) by the F-box protein Fbw7, a tumour suppressor 78 . Ablation of Nde1 in mice leads to microcephaly, possibly due to proliferative delays provoked by the persistence of cilia in progenitor neurons 77,79 .…”
Section: Cilium Disassemblymentioning
confidence: 99%